Characterization of nitrogen isotope fractionation during nitrification based on a coastal time series. Issue 8 (15th June 2022) - Haas, Sebastian; Rakshit, Subhadeep; Kalvelage, Tim; Buchwald, Carolyn; Algar, Christopher K.; Wallace, Douglas W.R.
Abstract: Isotopic enrichment factors are key to using stable isotope signatures in biogeochemical studies. However, these are typically determined in laboratory experiments and their applicability to environmental conditions is difficult to test. Here, we analyzed nitrogen stable isotope changes associated with nitrification in a coastal basin using weekly time‐series measurements of δ 15 N in particulate nitrogen, ammonium, nitrite, and nitrate. Two year‐long time series were selected as contrasting natural experiments in the ammonium‐rich, aphotic bottom water of Bedford Basin, Nova Scotia, Canada. In 2014, ammonia oxidation (AO) was associated with Thaumarchaeota and nitrite concentrations remained low (< 0.5 μ mol kg −1 ). In contrast, transient nitrite accumulation ( 8 μ mol kg −1 ) and a more rapid δ 15 NNH4 increase in the fall of 2017 were likely caused by ammonia‐oxidizing bacteria, associated with higher AO rates and, possibly, stronger nitrogen‐isotope enrichment ( 15 εAO ). Estimates of 15 εAO (21.8 ± 2.2‰, 24.1 ± 1.1‰) were derived empirically using Rayleigh models applied to field data from restricted periods during which the bottom waters approximated a closed system and influence on 15 εAO from other processes was demonstrably insignificant. Using a numerical reactive‐transport model, we found that the best fit for the δ 15 N data was obtained with 15 εAO values (18.9‰, 25.1‰) close to those determined by the Rayleigh models. The time series also revealed substantial ( 7‰) 15 N‐enrichment of the particulate nitrogen due to light‐independent assimilation of partially nitrified ammonium. Consistent with previous studies, these field‐based nitrogen isotope fractionation experiments suggest that the range of 15 εAO values relevant for marine systems may be narrower than determined in laboratory studies.